Mycetoma At An Unusual Site - Roy Aloke K R; Ghosh Sadhan K R; Gangopadhyay Debabrata; Das Jayasri (Wolters Kluwer Medknow Publications, 1996)
A case of mycetoma, caused by Nocardia species in a 18 year old urban boy, involving nape of neck and adjoining are and upper back, is reported.